Renewable Energy and Economic Growth: Evidence from the Sign of Panel Long-Run Causality - Apergis, Nicholas; Danuletiu, Dan Constantin (International Journal of Energy Economics and Policy, 2014)
Unlike previous renewable energy-growth studies, this study examines for the first time the relationship between renewable energy and economic growth for 80 countries under the Canning and Pedroni (2008) long-run causality test, which indicates that there is long-run positive causality running from renewable energy to real GDP for the total sample as well as across regions. The empirical findings provide strong evidence that the interdependence between renewable energy consumption and economic growth indicates that renewable energy is important for economic growth and likewise economic growth encourages the use of more renewable energy source. The presence of causality provides an avenue to continue the use of government policies that enhance the development of the renewable energy sector. Keywords: Renewable energy; Economic growth; Sign test; Panel countries JEL Classifications: C33; E23; Q20